Forest active restoration for silvopastoral use in Northwestern Patagonia: relative importance of the nurse effect - Chillo, María Verónica (2023)
Ecological interactions, such as facilitation among plant species, has been identified as key for restoration actions. The stress-gradient hypothesis predicts that facilitation increases under harsh environments, but disturbance type and nurse shrub characteristics may modify this prediction. We aim at assessing the effect of two interacting factors (herbivory pressure and light availability) and palatability of the nurse shrub on the importance of nurse effect for active restoration of mixed evergreen forests of northern Patagonia (Argentina) for silvopastoral use. We planted Austrocedrus chilensis seedlings under two silvopastoral use intensities (higher and lower according to livestock seasonal movements) and under three micro-site treatments (palatable shrub, non-palatable shrub, inter-canopy), and evaluated survival and growth during three consecutive years. Under higher use intensity (increasing stress of light availability as desiccation risk and herbivory) we found contrasting effects of the nurse effect on seedling survival and growth, but the palatability of nurse shrub had no effect. Under higher use intensity, seedling survival was lower, while growth was higher. Higher values of seedling survival were found under low use intensity inter-canopy micro-site. Under high use, the presence of a nurse shrub is important for summer seedling survival, indicating its role in avoiding desiccation. The same occurred for winter seedling survival, where a nurse shrub may decrease mainly trampling risk. We highlight the importance of considering the interaction between disturbance factors for the net outcome of the nurse effect in active restoration actions, as it may allow for diverse actions to restoration.